Defining mainframe transaction's signature with an XML Schema converting Cobol metadata into an XML Schema using regular expressions processing. - Burin, Edgardo (SOA webservices journal.)
Integrating mainframe applications into an SOA often carries the burden of dealing with metadata in the form of Cobol Copybooks. This metadata converted to an XML Schema format can be useful for a range of applications (from validation to creation of services). This article explains how to automate the conversion from Copybooks to XML Schema using regular expression logic.